The Influence of Green Marketing and Brand Image on Purchase Decisions for Environmentally Friendly Products (A Case Study of The Body Shop in Cirebon) - Meylina Safitri; Yusuf Yusuf (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2026)
The growing environmental awareness among consumers has increasingly shifted purchasing preferences toward eco-friendly products, prompting companies to adopt more sustainable business practices. Recognized as two salient factors that may steer consumer purchase decisions, particularly for environmentally oriented retail brands, green marketing and brand image form the focal constructs of this study. The research objective is to analyze their effect on purchase decisions regarding The Body Shop products in Cirebon. A quantitative approach underpins the study, utilizing data from 120 consumers analyzed via Structural Equation Modeling–Partial Least Squares (SEM-PLS). The empirical outcomes show that green marketing positively and significantly affects purchase decisions (T-statistics = 2.087; P-values = 0.037). Brand image also exhibits a positive and significant effect, but with a considerably stronger influence (T-statistics = 4.736; P-values = 0.000). The R-square value of 0.711 signifies that green marketing and brand image jointly explain 71.1 percent of the variance in purchase decisions. Thus, both green marketing and brand image substantively contribute to shaping consumer purchase decisions for The Body Shop products in Cirebon, with brand image holding greater sway. These findings suggest that companies should prioritize strengthening brand image while simultaneously implementing sustainable marketing strategies to more effectively elevate consumer purchase decisions. Future research may consider incorporating additional variables or broader sampling to further extend the generalizability of these findings.